(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article defines the subject and the structure of the educational environment of the institution of higher education. In accordance with the determined components of the educational environment such as physical conditions of the premises, the mode of educational process, the set of skills to be gained during this process, the practice and the scientific research of the students, the students’ vision of the educational environment and its evaluation have been emphasized. The ways of improvement of the educational environment of the institutions of higher education have been defined on the basis of the conducted research. The perspective of the further research lies in determining the means of updating the educational environment through the example of a particular educational institution.